2020
DOI: 10.1038/s41467-020-19410-8
|View full text |Cite
|
Sign up to set email alerts
|

Bryophytes are predicted to lag behind future climate change despite their high dispersal capacities

Abstract: The extent to which species can balance out the loss of suitable habitats due to climate warming by shifting their ranges is an area of controversy. Here, we assess whether highly efficient wind-dispersed organisms like bryophytes can keep-up with projected shifts in their areas of suitable climate. Using a hybrid statistical-mechanistic approach accounting for spatial and temporal variations in both climatic and wind conditions, we simulate future migrations across Europe for 40 bryophyte species until 2050. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 78 publications
2
43
0
Order By: Relevance
“…However, comparisons of altitudinal ranges of species in réunion island with those of continental mountain ranges revealed that the former are narrower than the latter (ah-Peng et al 2012). Furthermore, projections of species distribution models for Macaronesian endemic species onto future climatic layers pointed to an average decrease of suitable areas of 62-87% per species (Patiño et al 2016), which is comparatively higher than the 16-42% of range loss predicted for the european bryophyte flora (Zanatta et al 2020). Model predictions suggest that even the commonest endemic species would fit either the Vulnerable or endangered IuCN categories by 2070 (Patiño et al 2016).…”
Section: Island Conservation and Managementmentioning
confidence: 83%
“…However, comparisons of altitudinal ranges of species in réunion island with those of continental mountain ranges revealed that the former are narrower than the latter (ah-Peng et al 2012). Furthermore, projections of species distribution models for Macaronesian endemic species onto future climatic layers pointed to an average decrease of suitable areas of 62-87% per species (Patiño et al 2016), which is comparatively higher than the 16-42% of range loss predicted for the european bryophyte flora (Zanatta et al 2020). Model predictions suggest that even the commonest endemic species would fit either the Vulnerable or endangered IuCN categories by 2070 (Patiño et al 2016).…”
Section: Island Conservation and Managementmentioning
confidence: 83%
“…In contrast, Frullania fuscovirens in the TRF and Frullania chenii in the STF attached on the crown zones are adapted to intense radiation and drought stress in the forest canopy. These findings carry conservation implications for the potential impacts of climate change on epiphytic bryophyte distributions, as the changes in microclimatic conditions due to anthropogenic warming may results in the shift in their vertical distributions or in local extinctions (Pardow and Lakatos, 2013;Zanatta et al, 2020).…”
Section: Factors Structuring the Bryophyte-host Networkmentioning
confidence: 89%
“…Despite the predictive power of their ensemble modeling of D. involucrate , an important limitation in the present study is that we assessed future habitat suitability under two extreme dispersal assumptions (i.e., no dispersal and unlimited dispersal), which ignores the realistic rates and modes of dispersal of this species (Saupe et al., 2012 ). These assumptions are likely inaccurate, which could lead to overestimation of suitable habitat under the unlimited dispersal assumption or underestimation under the zero‐dispersal assumption (Engler & Guisan, 2009 ; Viana, 2017 ; Zanatta et al., 2020 ). For instance, Engler and Guisan ( 2009 ) assessed the potential impacts of climate change on habitat suitability of 287 mountain plants under four dispersal scenarios (unlimited dispersal, zero dispersal, realistic dispersal, and realistic dispersal with long‐distance dispersal events).…”
Section: Discussionmentioning
confidence: 99%